Primary abdominal intercostal hernia: Dream or clinical reality? - Michela Zanatta; Marcello Donati (International Journal of Abdominal Wall and Hernia Surgery)
The term intercostal hernia (IH) refers to conditions where either the lung or abdominal viscera herniate through a defect in the intercostal space. Abdominal viscera can herniate through an intercostal space with (transdiaphragmatic IH) or without (abdominal IH) an associated diaphragm injury. Primary IHs are extremely rare, with only one case previously described in the literature. Here, we present the second case of a primary spontaneous abdominal intercostal hernia reported in the literature. The computed tomography scan revealed no rib fractures or diaphragm injuries, but it did reveal that the patient had two extra lumbar ribs, with the hernial defect located between the 12th and 13th right rib. Primary spontaneous IHs are extremely rare, so it could be hypothesized that they might not truly exist as a distinct clinical entity, suggesting an unrecognized cause that would classify them as acquired hernias, such as an extra pair of ribs or congenital diseases.